SPACE WEATHER PARAMETERS CAPABLE OF INFLUENCING HEALTH OF A HUMAN BEING - Samsonov, S. N.; Manykina, V. I. (Одеські астрономічні публікації, 2012)
Space weather is a state of Earth-orbital space. The Sun and cosmic rays of high energy affect this state. As the main contribution to a space weather state is made exactly by the Sun then changes of solar activity parameters, and also the changes of geophysical parameters caused by such influence have been considered in this study. A condition of cardiovascular system of a person of volunteer groups has been considered as a condition of health of a human being. An experiment has been carried out within the framework of Russian-Ukrainian project "Geliomed" (http://geliomed. immsp.kiev.ua) [Вишневский и др.., 2009]. It has been found both the immediate influence of electromagnetic solar radiation and the influence of parameters of solar wind and interplanetary magnetic field on a condition of cardiovascular system of a human being mediated through geophysical parameters.